Analysis of the Role of Families in Supporting the Academic and Social Success of Children with Disabilities in Inclusive Schools - Andreas Heri Kurniawan (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study is conducted to examine the role of family support in improving the academic and social success of children with disabilities in inclusive elementary schools. Although inclusive education guarantees equal learning opportunities for all children, its implementation often faces challenges due to limited family involvement and weak collaboration between home and school. The purpose of this research is to evaluate the effect of family support on academic and social achievements of children with disabilities in an inclusive educational environment. A mixed research design with a convergent parallel model was used for the study whereby structured questionnaires and semi-structured interviews were distributed to 60 parents and 8 respondents respectively using correlation, simple linear regression, and thematic content analysis techniques. It was discovered that there exists a statistically positive significant correlation between family support and academic/social success of students with disability r = 0.682, p = 0.000 with a percentage contribution of 46.5%, R² = 0.465. Family emotional support, provision of academic guidance, and regular parent–teacher contact emerged as the most effective variables contributing to academic and social success. From this study, it is clear that successful inclusive education does not depend on school preparedness alone but also family participation and hence recommendation for more effective family-school models.